Outcome of Mifepristone in Induction of Labor in Pregnancy with Intrauterine Death - Sharifa, Jasmine; Zeba, Dilruba; Zesmin, Fahmida; Joy, Swapna Biswas (Faridpur Medical College Journal, 2025)
Induction of labor in delivery of intrauterine death cases is associated with higher incidences of prolonged initiation of labor. Mifepristone is thought to be the safest and cost effective modalities for induction of labor in pregnancy after intrauterine death. The aim of this study was to assess the outcome of induction of labor in intrauterine death with mifepristone. This prospective observational study was conducted at the Department of Obstetrics & Gynaecology in Faridpur Medical College & Hospital, Faridpur during July 2023 to June 2024. Total 95 pregnant women with intrauterine death at/after 28 weeks were interviewed after taking written informed consent. Participants were given mifepristone (200mg) orally 8 hourly for 48 hours. Bishop’s score was assessed before induction and after 24 and 48 hours of doses. Collected data was analyzed by the SPSS 25.0. The mean age of patients was 28.12±5.51 years. Maximum women were nulliparous (53.68%) and had gestation for >36 weeks (64.21%). The mean value of bishop's score significantly increased after 24 hours of induction, compared to on-administration value (4.87±1.55 vs 7.46±1.65, p<0.001). Overall, majority respondents (77.89%) had successful induction and had vaginal delivery. Nausea/vomiting (68.42%), dizziness (46.32%), abdominal crumps (10.53%) and fever (6.32%) were the common complications. The most prevalent complication was nausea and vomiting (68.42%). Faridpur Med. Coll. J. 2025;20(1): 41-45